Investigating for Photocatalytic Activity of Hybrid TiO2/Reduced Graphene Oxide and Application in Reducing VOCs - Thanh, Nguyen Thi Phuong; Danh, Nguyen Thanh; Nguyen, Tran Quang; Giang, Huynh Van; Chi, Tran Kim; Giang, Le Thuy Thanh; Trung, Tran Quang (Bulletin of Chemical Reaction Engineering & Catalysis, 2024)
In this study, rGO/TiO2 hybrid nanostructures (rGO : reduced Graphene Oxide)  have been successfully fabricated for the purpose of application in the treatment of volatile organic compound (VOCs) that harmful for the environment through the method of directly measuring the change in concentration of decomposed VOCs in real time under UV-excited conditions using a home-made measuring system. the results showed that hybrids TiO2 : rGONFs (reduced Graphene Oxide nano flake) samples with the weight ratio between two kind of material are 99%:1% and 98%:2% which reduced VOCs faster than 2 time intrinsic TiO2. The phenomenon of 2D materials involved in the hybrids lead to the fact that the photocatalytic activity of TiO2 had been significantly improved, this can be explained as follows: When heterogeneous hybrid was formed, because of the difference in energy levels of conduction band between two materials was negligible, heterojunction barrier is not too high this made the photogenerated electrons from TiO2 easily move through rGONFs under UV stimulation. This thing has significantly reduced the recombination of the generated carrier in TiO2 during irradiation, which lead to an increase in the lifetime of the carrier and make photocatalytic reaction of the assembly become more effective. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).